2019
DOI: 10.1155/2019/8629030
|View full text |Cite
|
Sign up to set email alerts
|

Use of Long-Acting Injectable Antipsychotic in an Inpatient Unit of a Community Teaching Hospital

Abstract: Background. Individuals with Schizophrenia Spectrum Disorders (SSD) often experience significant impairment in educational, occupational, and psychosocial functioning. The clinical benefit of long-acting injectable antipsychotics (LAIs) in the management of patients with SSD is well established. SSD patients who are nonadherent to treatment have lower disease relapse and readmission rates when prescribed a LAI, compared to oral antipsychotics. Despite the reported advantages of LAIs, their prescription rates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 20 publications
1
9
3
Order By: Relevance
“…The LAI prescribed most often was by far paliperidone palmitate followed by aripiprazole monohydrate while risperidone microspheres and first-generation LAI were prescribed in a small patient subgroup. These results are in contrast with the findings of Olayinka et al [19] who assessed LAI prescription rates in an inpatient setting and reported that 44% of a total of 43 patients with SSD were treated with an LAI. They found risperidone microspheres to be the most often used substance followed by paliperidone palmitate and haloperidol decanoate.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The LAI prescribed most often was by far paliperidone palmitate followed by aripiprazole monohydrate while risperidone microspheres and first-generation LAI were prescribed in a small patient subgroup. These results are in contrast with the findings of Olayinka et al [19] who assessed LAI prescription rates in an inpatient setting and reported that 44% of a total of 43 patients with SSD were treated with an LAI. They found risperidone microspheres to be the most often used substance followed by paliperidone palmitate and haloperidol decanoate.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar trends were obtained by Kishimoto et al in an inpatient setting in New York City [18]. On the other hand, in a hospital mainly serving low-income and uninsured population in Brooklyn, New York City, authors reported that 44% of inpatients were treated with LAIs at time of discharge [19]. Beside these three studies there are to our knowledge no other data evaluating the use of LAI in acute psychiatric inpatient settings; additionally, none of these studies analyzed LAI prescription rates in Europe.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The disease has positive psychotic symptoms (hallucinations and delusions) and negative psychotic symptoms [lack of motivation, decreased feeling of pleasure, emotional retardation ( 1 ). Its typical characteristics are cognitive and emotional abnormalities, which cause significant damage to the patient's education, occupation, and psycho-social functions ( 2 ). The aim of treating schizophrenia is clinical, social and personal remission and prevention of relapses ( 3 ).…”
Section: Introductionmentioning
confidence: 99%